The Contribution of Financial Literacy, Lifestyle, and Fintech to Generation Z Financial Management in Jepara - Aulya Pratiwi Sekarsari; Anna Widiastuti (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aimed to analyze the role of financial literacy, lifestyle, and financial technology in shaping the financial management of Generation Z in Jepara Regency. Research Methodology: A quantitative survey was conducted with 180 Generation Z respondents selected through random sampling using a structured, online questionnaire. Data were analyzed using partial least squares-structural equation modeling with SmartPLS software. This method was chosen for its ability to test complex relationships, support predictive analysis, and provide practical model interpretations for policy and program development. Results: Financial literacy positively and significantly affects financial management behavior and is the strongest factor. Fintech usage also has a positive and significant effect, whereas lifestyle has no significant relationship with financial management. The model explains 37.1% of the variance in financial-management behavior. Conclusions: Financial literacy and effective use of digital financial services are key to improving financial management among Generation Z. Lifestyle alone does not explain financial management behavior without financial knowledge. Limitations: This study is limited by its cross-sectional design and focus on a single geographic area, which may limit the generalizability of the findings across different regions and periods. Contributions: This study emphasizes practical contributions by providing clear guidance for policymakers, educational institutions, and financial technology providers to design targeted financial literacy programs, integrate digital financial education into youth initiatives, and develop fintech services that promote responsible financial behavior among Generation Z, particularly in non-urban contexts.